Research on distributed identity authentication mechanism of IoT device based on blockchain - Chen TAN; Meijuan CHEN; Ebenezer ACKAH Amuah (物联网学报)
Aiming to solve problems of the low compatibility and weak anti-attack ability of the Internet of things (IoT) centralized platform in the device identity authentication process,a blockchain-based distributed IoT device identity authentication architecture was proposed.The digital identity and related information were stored in the new block data structure,and a distributed IoT device identity authentication mechanism was proposed based on the cryptography related knowledge.At the same time,a device digital certificate issuance process and a detailed process of the identity authentication were designed.The security analysis of the proposed mechanism were carried out from the aspects of power constraints,device privacy protection,and ability to resist attacks among various entities.The performance of three aspects,which were security attributes,computational overhead and storage overhead,were compared and analyzed.The results show that the proposed identity authentication mechanism can resist a variety of malicious attacks,achieve highly secure distributed IoT identity authentication,and has certain advantages in the performance.